Local Marginalization in Batam Island as Industrial Cities in Border Region Indonesia: Where is The Role? - Otti Ilham Khair; Welasari Welasari; Catur Widiatmoko; Ratna Indriasari; Fitrisia Munir; Delmira Syafrini (ARISTO, 2022)
This study aims to evaluate the level of marginalization of local communities and analyze their participation in sustainable development on Batam Island as an Industrial city that is developing and bordering ASEAN countries. The research applied a descriptive qualitative research method with a case study approach and used the concept of gentrification, an implication of new industrial cities describing a phenomenon empirically. The results show that Batam Island, as one of the developing new industrial cities than other cities, cannot withstand the influx of people from outside the cities to work and settle there. As the center of industrial cities in Indonesia's border regions with Malaysia and Singapore, it has opened cooperation with developed countries with the support of globalization currents to have affected the urban system and destroyed many traditional regional models. This research found that local cities' development strategies are required through the collaboration of sub-state actors and must be planned under a more macroscopic framework so that local communities are not deeply marginalized as part of industrial cities' growth.